Role of total-totals stability index in forecasting of thunderstorm/non-thunderstorm days over Kolkata during pre-monsoon season (MAUSAM, 2007)
The thunderstorm activity over Kolkata during pre-monsoon months (March, April and May) has been studied using the radiosonde data of Kolkata (Dumdum). The objective of the study is to examine the utility of Total-Totals Index (TTI) in forecasting occurrence/non-occurrence of thunderstorm over Kolkata. The investigation reveals that Total-Totals Index can be preliminarily used as a predictor to differentiate thunderstorm and non-thunderstorm days. The probability of occurrence of thunderstorm is higher when Total-Totals Index value is higher. While the exact prediction of thunderstorm in all the cases, using the TTI alone, is obviously not possible as TTI alone does not describe the total atmospheric conditions. However, a significant forecast can be furnished by using a threshold value of Total-Totals Index.